The green house effect - Lim, Marie Shimin. (2013)
The Green House Effect is a feature writing project about green buildings in Singapore. It explores the rising popularity of environmentally friendly buildings and the impact it would have on Singaporeans in terms of energy savings and protection from the effects of global warming. Green buildings are defined as environmentally-friendly buildings which are constructed and maintained in a way that minimises damage to the Earth’s ecosystem and the natural environment. Such buildings are equipped with energy-producing abilities (such as solar power panels), energy-saving abilities (such as energy-efficient lighting and air-conditioning), rooftop gardens and an intelligent architectural design that maximises ventilation, natural lighting while minimising heat entry into the building interior. Green is a vague word and many businesses, commercial products and celebrities have labelled themselves ‘green’. However, in the The Green House Effect, we have adopted Singapore’s Building and Construction Authority’s definition of green building as a starting point. Green buildings are Singapore are recognised as so after receiving the Green Mark Award, a scheme launched by the BCA in 2005 to certify buildings that are environmentally friendly.